Bone-specific alkaline phosphatase activity is inhibited by bisphosphonates: role of divalent cations - Vaisman, Diego N. (2005)
Bisphosphonates (BPs) are drugs widely used in the treatment of various bone diseases. BPs localize to bone mineral, and their concentration in resorption lacunae could reach almost milimolar levels. Bone alkaline phosphatase (ALP) is a membrane-bound exoenzyme that has been implicated in bone formation and mineralization. In this study, we investigated the possible direct effect of three N-containing BPs (alendronate, pamidronate and zoledronate) on the specific activity of bone ALP obtained from an extract of UMR106 rat osteosarcoma cells. Enzymatic activity was measured by spectrophotometric detection of p-nitrophenol product and by in situ visualization of ALP bands after an electrophoresis on cellulose acetate gels. Because ALP is a metalloprotein that contains Zn²⁺ and Mg²⁺, both of which are necessary for catalytic function, we also evaluated the participation of these divalent cations in the possible effect of BPs on enzymatic activity. All BPs tested were found to dose-dependently inhibit spectrophotometrically mesasured ALP activity (93–42% of basal) at concentrations of BPs between 10⁻⁵ M and 10⁻⁴ M, the order of potency being zoledronate ≅ alendronate > pamidronate. However, coincubation with excess Zn²⁺ or Mg²⁺ completely abolished this inhibitory effect. Electrophoretic analysis rendered very similar results: namely a decrease in the enzymatic activity of the bone-ALP band by BPs and a reversion of this inhibition by divalent cations. This study shows that Ncontaining BPs directly inhibit bone-ALP activity, in a concentration range to which this exoenzyme is probably exposed in vivo. In addition, this inhibitory effect is most possibly the result of the chelation of Zn²⁺ and Mg²⁺ ions by BPs.